'In Search Of The Unbound Prometheia': A Comparative View Of Women's Activism in Two Quebec Industries, 1869-1908 - Ferland, Jacques (Labour/Le Travailleur, 1989)
Abstract One of the most salient features of women's earlier contribution to the labour movement in Quebec, during the late 19th and early 20th centuries, is the prominent and often militant role of female cotton workers. Long before they formed an industrial labour organization, the cotton "girls" rose persistently, in most mills, against various attempts to further appropriate absolute and relative surplus-value. After having formally joined forces with fellow male unionists, they carried with this activism a more acute challenge to managerial prerogatives and patriarchal standards of criminality in a major assault on child and gender-related abuses. The following essay explores, in a comparative mode and from the perspective of the workplace, why female cotton workers were more assertive and have left far greater evidence of their proneness to strike than other women operatives in the boot and shoe industry. It also focuses on two important episodes of female militancy at the Hochelaga and Ste. Anne mills in order to provide a socio-economic context to their activism and to witness how solidarity could evolve rapidly into estrangement over sensitive gender-related issues.